Phenological studies of some rain forest herbs in Peninsular Malaysia - Kiew, Ruth (Springer, 1986)
Trees in Peninsular Malaysia show seasonality for leafing (with two main peaks a year) and flowering (with a major season in February to May and in some species a second minor season in August and September) in spite of the variability shown by individuals. Didymocarpus platypus (Gesneriaceae) and Pentaphragma horsjieldii (Pentaphragmataceae) produce flowers throughout the year, although the flower buds of D. platypus "wait" and then open simultaneously. Staurogyne longifolia (Acanthaceae) and Phyllagathis rotundifolia (Melastomataceae; the latter flowers very occasionally) flower seasonally at the same time as trees. In addition, P. rotundifolia has two peaks of leaf production at the same time as trees. Leaves of these forest herbs expand very slowly and are long-lived (18 to 33 months). Leaves of most evergreen tree species live for between 13 and 14 months. Two strategies for survival are shown by these herbs. Pentaphragma horsfieldii and S. longifolia rely on the regular production of seed for their survival-seedlings are common in their populations and they flower and die earlier than Phyllagathis rotundifolia or D. platypus, which rely on a long-life with a lower level of reproduction. P. rotundifolia and D. platypus both produce annually at least three times the leaf area of the other two species. P. rotundifolia rarely produces fruits; its plants are potentially immortal with an evergrowing prostrate stem and it also commonly produces leaf cuttings from its fallen leaves. D. platypus is estimated to live for about 20 years.